Change in the making': Building on the past gender trends in CGIAR agricultural research - Burg, Margreet van der (Wageningen University & Research, 2018)
Presented by Margreet van ver Burg (Wageningen UR), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.